Atomic scale investigation of a novel metastable structure in aged Mg–Nd alloys. (1st March 2019) - Sun, B.Z.; Tan, J.; Zhang, H.X.; Sun, Y.H.
Abstract: Aged Mg-3.0 wt% Nd alloys were investigated by high angle annular dark-field scanning transmission electron microscopy. A hitherto unreported metastable phase designated β 3 can always emerge at the endpoints of β 1 particles. The crystal structure of β 3 phase is determined to an orthorhombic lattice (space group Cmcm ). With the {111} β 1 planes acting as the basal plane of growth, β 3 phase has three types of variants, which are related by a 120° rotation with respect to each other around the same [001] β 3 axis. In addition, several peculiar morphologies and further evolution of β 3 phase were also analyzed. Graphical abstract: A novel metastable β 3 phase in Mg–Nd alloys was found and determined to be an orthorhombic lattice with space group Cmcm . Meanwhile, there exist three types of variants ( V 1, V 2 and V 3 ) of β 3 phase, which are related by a 120° rotation with respect to each other around the same [001] β 3 axis.